Itinerario de una comunidad exclaustrada. Los religiosos del Colegio de Guadalupe frente a la ley de nacionalización de bienes eclesiásticos (1859-1908) - Strobel del Moral, Héctor (El Colegio de México, A.C., 2020)
On July 12, 1857, Benito Juárez signed a law nationalizing church assets, which included the elimination of male religious orders and the seizure of their possessions by the state. The community of the College of Guadalupe in Zacatecas was soon forced to dissolve and its monks to give up their habits. Nevertheless, some of the monks resisted. Despite their persecution by the liberal government, they adopted a series of strategies, such as traveling to other convents in cities occupied by conservative forces, creating new foundations and even reentering the college. When the liberals definitively defeated the conservatives in 1867, the Guadalupe brotherhood drastically shrunk. The majority preferred to become civilians, while others became priests. Nevertheless, a handful of monks continued living in the college, in defiance of the law. As time went by, the government began to tolerate their presence.